2015
DOI: 10.1093/nar/gkv455
|View full text |Cite
|
Sign up to set email alerts
|

ProtPhylo: identification of protein–phenotype and protein–protein functional associations via phylogenetic profiling

Abstract: ProtPhylo is a web-based tool to identify proteins that are functionally linked to either a phenotype or a protein of interest based on co-evolution. ProtPhylo infers functional associations by comparing protein phylogenetic profiles (co-occurrence patterns of orthology relationships) for more than 9.7 million non-redundant protein sequences from all three domains of life. Users can query any of 2048 fully sequenced organisms, including 1678 bacteria, 255 eukaryotes and 115 archaea. In addition, they can tailo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…To investigate the direct contribution of MICU1 on MCU function, we employed the yeast S. cerevisiae as a model system, which lacks homologs of all mammalian uniporter components (Bick et al, 2012;Cheng and Perocchi, 2015), as well as endogenous mt-Ca 2+ uptake activity Carafoli and Lehninger, 1971;Kovacs-Bogdan et al, 2014;Yamamoto et al, 2016). Previous results, including ours, have shown that Hs-MCU and Hs-EMRE are sufficient to drive Ca 2+ uptake in vitro into the matrix of isolated mitochondria Kovacs-Bogdan et al, 2014;Yamamoto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the direct contribution of MICU1 on MCU function, we employed the yeast S. cerevisiae as a model system, which lacks homologs of all mammalian uniporter components (Bick et al, 2012;Cheng and Perocchi, 2015), as well as endogenous mt-Ca 2+ uptake activity Carafoli and Lehninger, 1971;Kovacs-Bogdan et al, 2014;Yamamoto et al, 2016). Previous results, including ours, have shown that Hs-MCU and Hs-EMRE are sufficient to drive Ca 2+ uptake in vitro into the matrix of isolated mitochondria Kovacs-Bogdan et al, 2014;Yamamoto et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Our phylogenetic analyses, as well as a previous comparative genomics study (Bick et al, 2012), have highlighted a widespread co-occurrence of MCU and MICU1 across Metazoa, Plants and Protozoa, with the exception of Fungi. The presence of MCU homologs in several Ascomycota and Basidiomycota fungal clades devoid of a detectable MICU1, together with the absence of EF-hands containing proteins co-evolving with fungal MCUs (Cheng and Perocchi, 2015) and the existence of a MCU homolog that is sufficient to drive Ca 2+ uptake in mitochondria of D. discoideum (Kovacs-Bogdan et al, 2014), led to the hypothesis that MCU could exist independently of a Ca 2+ -sensing regulator. However, this hypothesis stems from the assumption that fungal MCU homologs per se are able to mediate mt-Ca 2+ uptake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This led to the successful application of phylogenetic profiling to a genome-wide analysis of S. cerevisiae (Marcotte et al, 1999), the discovery of novel Drosophila cilia genes (Avidor-Reiss et al, 2004), a screen for novel small RNA pathway components in C. elegans (Tabach et al, 2013a), and multiple components of a key mitochondrial uniporter (Baughman et al, 2011; De Stefani et al, 2011). In recognition of the method’s utility, web servers for comprehensive phylogenetic profiling continue to be developed (Cheng and Perocchi, 2015) and coevolution metrics have been incorporated in some major interactome databases (von Mering et al, 2005; Szklarczyk et al, 2015). …”
mentioning
confidence: 99%